2015
DOI: 10.1007/s11999-014-4091-y
|View full text |Cite
|
Sign up to set email alerts
|

The EQ-5D-5L Improves on the EQ-5D-3L for Health-related Quality-of-life Assessment in Patients Undergoing Total Hip Arthroplasty

Abstract: Background The EQ-5D is a generic health survey that can be used to compare improvement across different interventions, measure changes in health-related quality of life over time, or to explore cost-effectiveness among treatments, hospitals, or providers. The original EQ-5D survey has three response options for each of five health dimensions; however, with so few response options, ceiling and floor effects are problematic in some populations. A new version, called the EQ-5D-5L, was developed, which gives resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 19 publications
7
45
2
Order By: Relevance
“…[52][53][54]56,57 Some studies have shown a high level of agreement between the two measures. 50,51,54,57,59 There have been no studies comparing the two instruments in critical care survivors.…”
Section: Cost-utility Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54]56,57 Some studies have shown a high level of agreement between the two measures. 50,51,54,57,59 There have been no studies comparing the two instruments in critical care survivors.…”
Section: Cost-utility Analysismentioning
confidence: 99%
“…49 Several studies have compared the EQ-5D-3L and the EQ-5D-5L in different countries in both general population samples and specific patient groups, but none of these has examined the two measures in critical care patients. [49][50][51][52][53][54][55][56][57][58][59] The aim of the present study was to compare EQ-5D-3L scores with EQ-5D-5L scores in critical care survivors in the UK. The sample for the present study comprised 359 patients treated at any of the 20 participating UK centres.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Within the UK, the EuroQol-5D (EQ-5D) is the most commonly used preference-based measure [3], and the one recommended by NICE for HTA submissions [4]. Since 2011, a five-level version of the EQ-5D (EQ-5D-5L) has replaced the previous three-level version (EQ-5D-3L) [5], and emerging evidence indicates improved psychometric performance [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the positive emerging evidence for the psychometric properties of the ICECAP-A [32][33][34][35] and EQ-5D-5L [6][7][8][9], no evidence is yet available for the context of opiate dependence. Even though some supporting evidence for the EQ-5D-3L and other similar health-focused measures exists for this context [36][37][38][39], such measures are used with caution in economic evaluations [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many previous studies conducted to compare the psychometric properties of EQ-5D-3L and EQ-5D-5L in many population and settings, for instances study in general population in the Netherlands 7 and in Greece 8 study in healthy and/or young individuals in Portugal 9 , study in six Euroepan countries (Denmark, England, Italy, the Netherlands, Poland, and Scotland) involving eight patient groups with chronic conditions (cardiovascular disease, respiratory disease, depression, diabetes, liver disease, personality disorders, arthritis, and stroke) 10 , study in population with chronic conditions in Canada 11 , study in osteoarthritis patients in Canada 12 , study in stroke patients in Poland 13 , study in patients with Total Hip Arthroplasty in Sweden 14 , study in Type 2 diabetes mellitus patients in Thailand 15 and in China 16 and study in rheumatoid arthritis patients in UK 17 Most of studies found that EQ-5D-5L had better psychometric properties compared to 3L. However, to the best of our knowledge such study has not been conducted in Indonesian population.…”
Section: Introductionmentioning
confidence: 99%